Mental Health Officer Experience in Handling People with Mental Disorders in the Public Healthy Center of Lamongan Regency - Eka Lestari, Wahyu Agustin; Yusuf, Ah; Tristiana, Rr. Dian (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2020)
Introduction: The experience of a mental health practitioners can affect the quality of mental health services. Mental health practitioners have various obstacles in the treatment of mental disordered patients. The aim of this research is to know the experience mental health on treating mental disordered patients in health center.Method: This study uses qualitative research with a phenomenological approach. Sampling was conducted by purposive sampling with a sample size of 15 participants. Data were collected using with observation and semistructured in-depth interview. Thematic analysis was performed using Colaizzi steps.Results:  The experience of mental health practitioners includes obstacles, motivation, and ways to overcome obstacles in dealing with mental patients. Obstacles faced by mental health practitioners come from mental disorders patients who do not want to take medicine and do physical or verbal violence against mental health workers, besides the lack of family support and lack of human resources so that health practitioners have difficulty in caring for mental disorders patients, but can be overcome with motivation education of mental health practitioners in treating mental patients, collaboration with cross-sectoral, improving the quality of human resources with CMHN training, socialization in the community and approach to the family.Conclusion: Experience can affect the level of knowledge and ability of mental health practitioners in handling mental disordered patients. The result of this research is expected to be used as both supporting data and references in increasing the quality of mental health service especially in health center work area.